Micro- and nano-celluloses derived from hemp stalks and their effect as polymer reinforcing materials. (1st October 2020) - Kassab, Zineb; Abdellaoui, Youness; Salim, Mohamed Hamid; Bouhfid, Rachid; Qaiss, Abou El Kacem; El Achaby, Mounir
Graphical abstract: Highlights: Micro- and nanocelluloses were successfully produced from hemp stalks. Extracted CMF, CNC and CNF were characterized using SEM, AFM, TGA, FTIR, and XRD. CNC and CNF showed a high reinforcing ability to improve PVA mechanical properties. Transparent and mechanically strong PVA based nanocomposites were produced. Abstract: Fiber-reinforced polymers have emerged as one of the most popular methods to improve the polymers' characteristics owing to their prominent properties. This study aimed to investigate the properties of cellulose microfibers (CMF), cellulose nanocrystals (CNC) and cellulose nanofibrils (CNF) extracted from hemp stalks, then their effect as reinforcement for the PVA-polymer. CMF have been extracted from hemp stalks with a diameter and yield of 16.96 μm and 63 %, respectively. Needle-shaped CNC were obtained from CMF using sulfuric acid hydrolysis at two hydrolysis times, while CNF exhibited a web-like structure obtained using TEMPO-oxidation followed by mechanical treatment. Cellulose derivatives were utilized to develop cellulose-based PVA composites; their transparency, chemical structure, thermal stability and mechanical properties were investigated. The incorporation of nanocellulose demonstrated a significant increase in mechanical properties compared to the neat PVA. The extracted nanocellulose could be used as nanofillers for the preparation of transparent and mechanically strong PVA-based nanocomposites.